STRATEGI PEMASARAN KERIPIK TEMPE SANAN DI KOTA MALANG BERDASARKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Indriani Indriani; Rahayu Relawati; Livia Windiana (Jurnal Sosial Ekonomi Pertanian, 2020)
A good marketing strategy needs to be applied in Tempe chips business. The purpose of this investigation is how the business description Tempe chips business & determine an effective marketing strategy based on the Analytical Hierarchy Process (AHP) business criteria on costs, sales value and profits. This method utilized a random sampling method with several samples studied by 23 industries. Analytical Hierarchy Process (AHP) is applied to determine between alternative kiosk strategies and consignment. The result showed that the more effective strategy was using its kiosk. Analytical Hierarchy Process analysis results produce a value of less than 1, means that the effect of CR <0.1 is a consistent assessment. The calculation at the Eigen stage provides 1 and continues for the Lamda Max calculation of 2.354 and the CI of -0.332 and continues at the final count. The final result of the calculation of CR = -1,662. So it arguably to be consistent. The perfect strategy choice is the kiosk itself, and it can be seen from the results of the analysis with the Analytical Hierarchy Process method.